The Impact assessment of abattoir waste facility discharge on water in Osogbo, Nigeria. Issue 1 (1st January 2019) - Akanni, Ayotunde; Ogbiye, Adebanji; Onakunle, Olumuyiwa
Abstract: This study investigates the effects of indiscriminate disposal of abattoir waste into water bodies in the Aregbe area abattoir of Osogbo the capital city of Osun state, Nigeria. The samples for the study were gotten from the point source into the streams and wells of close proximity to the abattoir facility. The physiochemical and bacteriological parameters of the water bodies were analyzed and compared to the World health organization limits for discharge and use. The observed physicochemical and bacteriological parameters were Color, Odor, Temperature, pH, Alkalinity, Turbidity, Total hardness, Appearance, Calcium Hardness, Chlorine ion, Magnesium ion, Dissolved Oxygen and Total Coliform bacteria using the standard procedure in the Standard Methods for the Examination of Water and Wastewater Part 1000. It was observed that the Color, Dissolved oxygen and Total coliform exceeded the limits set by the world health organization. The fairly poor performance of the water bodies is due to the carrying capacity which in coming years will be exceeded. The indicators of the given water quality parameters give rise to future studies on the state of the water bodies in Nigeria.